Evolution of Gaas capping layer on in0.5Ga0.5As/Gaas quantum dots structure - Aryanto, Didik (2010)

(untitled)
Self-assembled InxGai_xAs/GaAs quantum dots were grown with and without GaAs capping layer. Effect of different growth condition on the capping layer was studied using atomic force microscope (AFM). The optical properties o f capped quantum dots structure was investigated by photoluminescence (PL) measurements. AFM images of the uncapped quantum dots showed dots with small size and high density. Surface morphology of the dots changes after being capped with thin GaAs layer using different growth conditions. The dots become larger in size and are elongated in the [ 1 10] direction during the growth temperatures o f 550°C for the GaAs capping layer. This is caused by the redistribution and intermixing of indium atom during the capping process. In another condition, whereby the GaAs strain reducing layer (SRL) were grown at 550°C in between the quantum dots layer and the GaAs capping layer which were grown at 650°C, the surface were flat. This indicates that the dots are completely embedded. Consequently, PL spectra of the dots with different capping layer process present different peaks position, line-width and intensity. However, growth condition of the capping layer is an important factor affecting the structural and optical properties of the dots structures, which should be taken into account in building stacked quantum dots laser.